Application and Optimization of neural networks for decision support ON EXCHANGE MARKET (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of investigation of developing neuron-fuzzy system that can be used as a decision support tool on the currency market are presented. The algorithm of trading signals forming is created, the most important technical indicators are chosen, the training selection is formed, and the neuron net is created and tested. The precision of developed model exceeds linear and quadratic regressions.